Innovation for Society: Towards a Typology of Developing Innovations by Social Entrepreneurs. Issue 1 (2nd January 2018) - Lubberink, Rob; Blok, Vincent; van Ophem, Johan; van der Velde, Gerben; Omta, Onno
ABSTRACT: Social entrepreneurs develop important innovative solutions for complex societal challenges. This exploratory article provides a typology of different approaches by which social entrepreneurs develop such innovations. This typology is based on their engagement in anticipation, reflexivity, stakeholder inclusion and deliberation, responsiveness and knowledge management, during the development of their innovation. Following from quantitative analyses of data from self-assessment questionnaires and subsequent contextualization, the findings reveal four distinctive ways to successfully develop innovative solutions for societal problems. This article therefore contributes to our understanding of the innovation process by which social entrepreneurs develop social innovations.